A hybrid neural network for hyperspectral image classification. Issue 1 (2nd January 2020) - Li, Jiangyun; Liang, Binxiu; Wang, Yuhao
ABSTRACT: Recent research shows that deep learning-based methods can achieve promissing performance when applied to hyperspectral image (HSI) classification in remote sensing, some challenging issues still exist. For example, after a number of 2D convolutions, each feature map may only correspond to a unique dimension of the hyperspectral image. As a result, the relationship between different feature maps from multiple dimensional hyperspectral image can not be extracted well. Another issue is information in extracted feature maps may be erased by pooling operations. To address these problems, we propose a novel hybrid neural network (HNN) for hyperspectral image classification. The HNN uses a multi-branch architecture to extract hyperspectral image features in order to improve its prediction accuracy. Moreover, we build a deconvolution structure to recover the lost information in the pooling operation. In addition, to improve convergence and prevent overfitting, the HNN applies batch normalization (BN) and parametric rectified linear units (PReLU). In the experiments, two public benchmark HSIs are utilized to evaluate the performance of the proposed method. The experimental results demonstrate the superiority of HNN over several well-known methods.